The Influence of Work Engagement and Knowledge Sharing on Nurse Performance - Nyoman Putu Martini, Ni; Rahayu Niwidadi, Sri; Herlambang, Toni; Qomariah, Nurul (International Journal of Management Science and Information Technology, 2024)
Human resources who serve as officers or employees in a company or institutional organization are always considered a vital asset for an organization. Performance or work achievement can be interpreted as achieving work results in accordance with the rules and standards that apply to each organization. Performance can also be said to be the result or output of a process. The purpose of this research is to find out directly the influence of work engagement and knowledge sharing on employee performance at RSD dr. Soebandi Jember. The total sample in this study was 171 inpatient nurse respondents with a minimum work period of 3 years. Descriptive analysis is used to determine the respondent's description. Validity test and reliability test for the validity and reliability of research data. Hypothesis testing was also carried out in this research. The research results show that work engagement and knowledge sharing partially have a positive and significant effect on the performance of RSD dr. Soebandi Jember.